STRATEGI GURU MENGATASI SPEECH DELAY: STUDI KASUS DI SD INKLUSI - Venti Mawarni; Danti Pujiati; Vera Yulia Harmayanthi (Universitas Muhammadiyah Jakarta, 2023)
ABSTRACT Research topics that discussed speech delay at the age of elementary school children were not widely carried out. However, research reports on similar topics for early childhood could be found easily. Therefore, the authors focused on describing the steps taken by teachers to deal with the children with speech delay, ranging from language problems, intervention programs, and academic development in schools to socio-emotional development. A qualitative approach with case study methods through interviews with informants and document studies was used in this study. Data collection was collected based on the interview guide developed by Fitriyani and Taseman. The results show that the way of the teachers deal with the children who have speech delays by (1) paying attention to language development by clarifying lip movements and hand signals when speaking, as has been done by speech therapy and conducting personal communication and interaction, (2) creating an open relationship between teachers, parents and psychiatrists to provide appropriate treatment (3) providing additional equal learning assistance outside class hours and applying lower standards of academic progress, (4) collaborating with parents and friends to reduce negative behavior. The attitude of teachers who are patient and nurturing to deal with ABK with speech delays in class is very necessary so that ABK does not drop out of school.Keywords: speech delay, school children, strategy